Tuning the p‐Orbital Electron Structure of s‐Block Metal Ca Enables a High‐Performance Electrocatalyst for Oxygen Reduction. Issue 51 (11th October 2021) - Lin, Zhiyu; Huang, Hao; Cheng, Ling; Hu, Wei; Xu, Pengping; Yang, Yang; Li, Jianmin; Gao, Feiyue; Yang, Kang; Liu, Shuai; Jiang, Peng; Yan, Wensheng; et al.
Abstract: Most previous efforts are devoted to developing transition metals as electrocatalysts guided by the d‐band center model. The metals of the s‐block of the periodic table have so far received little attention in the application of oxygen reduction reactions (ORR). Herein, a carbon catalyst with calcium (Ca) single atom coordinated with N and O is reported, which displays exceptional ORR activities in both acidic condition ( E 1/2  = 0.77 V,  0.1 m  HClO4 ) and alkaline condition ( E 1/2  = 0.90 V,  0.1 m  KOH). The CaN, O/C exhibits remarkable performance in zinc–air battery with a maximum power density of 218 mW cm –2, superior to a series of catalysts reported so far. X‐ray absorption near‐edge structure (XANES) characterization confirms the formation of N‐ and O‐atom‐coordinated Ca in the carbon matrix. Density functional theory (DFT) calculations reveal that the high catalytic activity of main‐group Ca is ascribed to the fact that its p‐orbital electron structure is regulated by N and O coordination so that the highest peak ( E P ) of the projected density of states (PDOS) for the Ca atom is moved close to the Fermi level, thereby facilitating the adsorption of ORR intermediates and electron transfer. Abstract : A catalyst of s‐block metal Ca‐based single atom is realized by tuning the p‐orbital electron structure of Ca active centers through coordinated N and O atoms, which exhibits excellent oxygen reduction reaction activity and durability, superior to a series of catalysts.